الشفعة الإدارية كقيد على المعاملات العقارية الخاصة بالأجانب - بحري كمال, مصطفاوي خليصة (Universté ELOUEd-جامعة الوادي, 2020)
يضمن المشرع الج ا زئري للأجانب من حيث الأصل تملك العقا ا رت في الج ا زئر انسجاما مع القواعد القانونية المستقرة على المستوى الدولي من ضرورة الاعت ا رف للأجنبي بالشخصية القانونية وما يترتب عليها من إق ا رر حقه في التملك ولكن ذلك ضمن ضوابط وقيود محددة تضمن المحافظة على النظام العام وتحمي المصلحة الوطنية وهذا ما كشف عنه المشرع الج ا زئري حيث سمح للأجانب من حيث المبدأ بتملك العقا ا رت عن طريق مختلف التصرفات القانونية التي تنتج آثارها حال حياة المتعاقدين وهذا ما يتجلى في حرية كل المعاملات التي تتم بين الاحياء والتي يقوم بها أشخاص طبيعيون أو معنويون من جنسية أجنبية والتي أخضعها المشرع إلى جانب القيود المفروضة بحكم القواعد العامة إلى قيود من نوع خاص تتمثل في سلسلة من الرخص المسبقة التي يتعين الحصول عليها قبل مباشرة أي تصرف قانوني في ملكيته للعقار وهذا ما جعل الأشخاص الأجانب يخضعون لمثل هذه القيود التي تكون سببا ودافعا لاستعمال الدولة لحقها في ممارسة الشفعة لتملك هذه العقا ا رت والمحافظة على وعائها العقاري حماية لسيادتها الوطنية على إقليمها.Of the effective means which might be used by the public authority to enrich the real-estate coffer of the state، as well as to serve for the public benefit، the right of pre-emption was used in order to obtain the real-estates needed to achieve projects of public benefit and to perform the tasks assigned to said projects، especially observation of the real-estate market and the limiting of speculation which، after its dependency on the acting policy of the state، turned to depending on the guarding and monitoring policies of the state and the Algerian legislator through the legislations and specialized orderly texts، which allow for the rights of pre-emption as a means to protect real-estate property and fight tax evasion. The goal of following this method by the state is to enforce its authority and monitor the real-estate transactions and find incomes for the state to support the public fund. In this work frame، legal texts remain without a scientific embodiment due to the lack of conflict in this matter and that is evident in the lack of court orders in this field، as well as the absence of organizing texts to clarify the conditions and procedures of practicing this right، obligatory to be followed by the state and its affiliated public bodies.
مذكرة ماستر
Keywords: تملك العقا ا رت-والمحافظة على وعائها العقاري حماية لسيادتها الوطنية على إقليمها; public authority to enrich-obligatory to be followed by the state and its affiliated public bodies